MAE572 : Problem solving in mathematics / Faculty of Education - UiTM, Faculty of Education (Universiti Teknologi MARA (UiTM), 2023)
This course is designed to introduce prospective elementary and secondary teachers to both theory and practice related to mathematical problem solving in schools. Students will explore pedagogical issues and participate in a variety of exercises, problems, and investigations as they explore secondary and primary-school mathematics concepts from a problem solving perspective in an interactive manner. The problems are of a variety of types and may include problems involving puzzles or patterns, word problems, algebra problems, counting and probability problems, problems dealing with geometry, and other mathematical problems. The emphasis is on exploration of various mathematics contexts to learn mathematics, to pose problems and problem extensions, to solve problems, and to communicate mathematical demonstrations.